(untitled) (Pakistan Journal of Science, 2023)
The studies on genetic diversity of Channa punctatusby using molecular markerswere carried out amongst the different groups of wild populations to investigate the genetic structureby Randomly Amplified Polymorphic DNA (RAPD) marker and the levels of polymorphism and similarity. The samples were collected from different five locations viz., Chashma Barrage at RiverIndus near District Mianwali, Qadirabad Barrage at Chenab River, Tehsil Wazirabad, DistrictGujranwala, Balloki barrage at Ravi River, Tehsil Bhai Pharo, District Kasur, Trimu Barrage at the junction of Chenab and Jhelum Rivers near District Jhang and Taunsa Barrage at Indus River near Tehsil Kot Addu District Muzaffar Garh. RAPD data for Jaccard’s coefficient by following the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) for Hierarchical Clustering of the similar groups on the basis of similarity amongst the genotypes. The dendrogram divided the randomlyselected individuals of the five populations into four classes/clusters; 17 members in first cluster/class,4 samples in second cluster/class and 2 samples in the third and fourth class/cluster.